Hollow polyhedral ZnCo2O4 superstructure as an ethanol gas sensor and sensing mechanism study using near ambient pressure XPS. Issue 40 (30th September 2021) - Yuan, Guotao; Zhang, Hui; Cheng, Yufeng; Zhong, Yihong; Zhuo, Qiqi; Sun, Xuhui
Abstract : ZnCo2 O4 hollow polyhedrons assembled by small nanoparticle building blocks were prepared and exhibited high response to ethanol. NAPXPS spectral indicate that oxygen abosorbed on the surface can react with ethanol molecules to form carboxylates. Abstract : To assemble small nanoparticles into a hollow polyhedron superstructure as a sensing material is a promising approach to improve the performance of metal-oxide–semiconductor gas sensors. In this study, ZnCo2 O4 hollow polyhedrons (ZnCo2 O4 HP) assembled by small nanoparticle-building blocks were prepared by simple one-step calcination of ZIF-67/ZIF-8 composites. Benefiting from rich active sites and abundant oxygen defects, ZnCo2 O4 HP exhibited high response (∼0.7 ppm −1 ) and low limits of detection (1 ppm) to ethanol vapor at a temperature of 200 °C compared with other similar ethanol sensors. The sensing mechanism was investigated to identify the underlying surface chemical processes in different atmospheres by operando near ambient pressure X-ray photoelectron spectroscopy (NAPXPS). The obtained spectral data indicated that oxygen adsorbed on the surface as active oxygen could react with ethanol molecules, which were decomposed into carboxylates. The present study provides strategies for the rational design of AB2 O4 materials, as well as an advanced method for the study of its sensing mechanism.